The promising but challenging case of humility as a positive psychology virtue. Issue 2 (2nd April 2016) - Hill, Peter C.; Sandage, Steven J.
Abstract: In maintaining that virtue is a legitimate concept worthy of empirical study, a strong situationist approach to the study of behavior is countered. An earlier analysis is then drawn upon to maintain that virtue has the capability of integrating several themes in positive psychology: ethics and health, embodied character, strength and resilience, communally embedded, meaningful purpose, and capacity for wisdom. The six themes are used to provide a framework for considering the unique case of moral and intellectual humility as a virtue.